Drug Safety for Children — International Monitoring Data for 50 Years - B. K. Romanov; Yu. V. Olefir; R. N. Alyautdin; S. V. Glagolev; V. A. Polivanov; L. I. Ilienko; S. P. Alpatov; N. V. Bogush; N. M. Buyanova; I. V. Ganshina; G. O. Dibirova; N. B. Dmitrieva; et al. (Безопасность и риск фармакотерапии, 2019)
The review article presents a summary of adverse drug reactions (ADR)  in children, information about which was received in 1968–2018 in the International database VigiBase (Uppsala monitoring center, UMC).  Of the  18.4 million Individual Safety Case Reports (ICSR)  received over  50 years by VigiBase, 1.47 million ICSR contain information on the  safety of pharmacotherapy in patients under the  age of 18,  including: 34 510  reports contain information on ADR  in children under the  age  of 27 days, 415  678  — in children aged  28 days  to 23 months, 613 676 — aged 2 to 11 years and 405 202 ICSR — in patients aged 12 to 17 years inclusive. During 2018  141 655 ICSR ADR of children in VigiBase was received. The most common reason for submitting reports on adverse effects in children was vaccines, antibiotics, non-steroidal antiinflammatory drugs, analgesics-antipyretics, anti-acne and valproic acid. The most common side effects of drugs in children were the following ADR: hyperthermia, rash, vomiting, nausea, urticaria, diarrhea, itching, headache, erythema at injection site, convulsion. Separate data on 6 age groups about 10 most frequent ADR in children and  about 10 medicines which ICSR most often arrived in VigiBase for 50 years and for 2018  are given.